Topological materials for helicity-dependent THz emission - Mannan, A; Saboon, Y; Xia, CQ; Damry, DA; Schoenherr, P; Prabhakaran, D; Herz, LM; Hesjedal, T; Johnston, MB; Boland, JL (IEEE, 2023)
Topological insulator (TI) materials are emerging as novel materials for spintronic applications. Here, we demonstrate helicity-dependent THz emission from Dirac semi-metal Cd 3 As 2 nanowires and used scattering-type scanning optical microscopy (s-SNOM) to identify potential single nanowire candidates for device applications. The preliminary investigation data of a candidate nanowire shows a homogenous topography and constant dielectric function in the MIR range. Indicating high-quality crystalline growth ideal for topological characterization.